Teste de caminhada de seis minutos e síndrome da fragilidade : repercussões na modulação autonômica da frequência cardíaca - Farche, Ana Claudia Silva (Universidade Federal de São Carlos, 2016)
Physical exercise is considered as a key in frailty syndrome treatment. However, until this moment, HR autonomic evaluation after exercise was not explored. This type of analysis would be important, once the presence of autonomic imbalance after performing exercise is related with cardiovascular events and sudden death. Moreover, this syndrome has been associated with deficits in the autonomic control of heart rate (HR). In this context, the aims of this study were to evaluate the performance in the 6-minute walk test (6MWT) and the heart rate autonomic modulation at rest and in recovery period in frail, pre-frail and non-frail elderly. The RR intervals of 49 elderlies were collected by a heart rate monitor (S810i Polar ®) at rest, during the 6MWT and in recovery period. Heart rate variability analysis was performed by linear analysis (spectral components) and non-linear analysis (symbolic and normalized complexity indexes). Frail group showed shorter distance walked than other groups (F= 197,8 ± 132; PF= 441,2 ± 132; R= 568,3 ± 176,2). No significant differences between groups were observed in supine rest. Changes in autonomic modulation were observed only in non-frail group in recovery period and demonstrated by symbolic analysis (0V%pre= 25,7 ± 15,5; 0V%post= 32,5 ± 15,8; 2LV%pre= 7,9 ± 4,16; 2LV%post= 5,33 ± 3,67). Despite distance walked similar to non-frail, pre-frail group presented no changes in autonomic modulation after exercise. This results indicates that regulation deficit in autonomic nervous system is already present in the beginning of the frailty process.
Keywords: Fragilidade; Teste de caminhada de seis minutos; Variabilidade da frequência cardíaca; Exercício; Recuperação; Frailty; Six-minute walk test; Heart rate variability; Exercise; Recovery; CIENCIAS BIOLOGICAS